If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 5x + 4 + 9 = 4x + 4 + 9x Reorder the terms: 4 + 9 + 9x + 5x = 4x + 4 + 9x Combine like terms: 4 + 9 = 13 13 + 9x + 5x = 4x + 4 + 9x Combine like terms: 9x + 5x = 14x 13 + 14x = 4x + 4 + 9x Reorder the terms: 13 + 14x = 4 + 4x + 9x Combine like terms: 4x + 9x = 13x 13 + 14x = 4 + 13x Solving 13 + 14x = 4 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 13 + 14x + -13x = 4 + 13x + -13x Combine like terms: 14x + -13x = 1x 13 + 1x = 4 + 13x + -13x Combine like terms: 13x + -13x = 0 13 + 1x = 4 + 0 13 + 1x = 4 Add '-13' to each side of the equation. 13 + -13 + 1x = 4 + -13 Combine like terms: 13 + -13 = 0 0 + 1x = 4 + -13 1x = 4 + -13 Combine like terms: 4 + -13 = -9 1x = -9 Divide each side by '1'. x = -9 Simplifying x = -9
| -3-4(3+5p)=-155 | | [7-4x]=5 | | 3/5(5m+15)=12 | | 12-3=m+4 | | 10(4x+10)=4(x+7) | | -0.25+1.75x=-1.75+2.25x | | -7+2r=-7+5r | | (7+4i)*(7+4i)= | | 7x+8=232 | | 2(24x-3.2)=4(10x+4.5) | | (2x+20)(6x-38)= | | -8(z-6)=-8z-7 | | 2k-3=15 | | 1762=598-24.25a | | 2-6b=-58 | | 11x-66x=5x | | 5.1-7p=(-9.9) | | 3b+b+40= | | -3x+2.5=1.5(x+4) | | 3453253453452345235235325+456456464564646464+x=1 | | 2x^4+3x^3-11x^2-9x+15=0 | | x+1=77 | | -1.81=.5w+3.07 | | 3000c-900=3750 | | 6(x-4)+2x=8x+12 | | -18=15-3(6c+5) | | . 7x+1=2x+6 | | 6x+5=5x-10 | | x+8=3(x+2) | | 3(y+2)-2=16 | | ((5x+3-2)*27)*5=23-4 | | .34=(-1.53)-4h |